Metabolomic and Transcriptomic Responses of Argopecten irradians concentricus to Thermal Stresses - Song, Junlin; Liu, Bo; Wang, Chunde (Frontiers in Marine Science, 2022)
The bay scallop southern subspecies, Argopecten irradians concentricus, which is widely cultured in southern China waters, is a eurythermal animal that is more adaptive to high-temperature waters but less tolerant to low-temperature waters. Despite that temperature is one of the most dominant environmental factors affecting dramatically its growth, survival, and hence production, the mechanism underlying the responses to thermal stress has not been explored in this animal. In this study, transcriptomic and metabolomic analyses were carried out in the adductor muscles of the bay scallop southern subspecies exposed to low and high thermal stresses. Transcriptomic analyses revealed that differentially expressed genes (DEGs) were enriched in the calcium ion, kinase activity, phosphatase activity, and lipid-related pathways in the group exposed to thermal stress, while most DEGs were enriched in the RNA processing pathways in the group exposed to low-temperature thermal stress. A large number of differentially expressed transcription factors involved in oxidation-reduction process, membrane-related pathways, transmembrane signaling receptor activity, and transduction-related pathways were induced by exposure to thermal stress. Results from metabolomic analyses showed that the retinol metabolism, inositol phosphate metabolism, and phosphatidylinositol pathways may be involved in the responses to high thermal stress, while more signaling pathways were enriched in the group exposed to low thermal stress. Integrated analyses of the transcriptomic and metabolomic data indicated that the degradation of valine, leucine, and isoleucine and the tricarboxylic acid cycle may be the major events induced by low and high thermal stress, and the retinol pathway may play critical roles in the responses of the scallops to high thermal stress. It seems that the bay scallop southern species have evolved distinct pathways in dealing with low and high thermal stress. Our results may provide useful information for marker-assisted selection of high-resistant strains in this scallop.